The aeronautic african security : the autistic communication in the Congolese DRC collective civil aeronautical security - (:unkn) unknown (My University, 2017)
The Democratic Republic of Congo (DRC) was one of the best models of aeronautical exploitation in Africa during colonization and over a couple of decades after independence to the extent of being congratulated by the International Air Transport Association (IATA). Today, in contrast, this huge central African country (DRC) is the bad student in world civil aviation in terms of security and the worst in terms of air accidents and disasters since the sector was liberalized in 1978. The consequence is that ORC has been blacklisted by the European Union since 2005. In the collective memory and the media, DRC is associated with crashes and air disasters so that every lime there is a plane crash anywhere in the world, reference is made to ORC. This research questions the issue of communication within organizations. New paradigms of air accidents are questioned with the aim of their prevention upstream in air transport. The main research question is about communication in civil aeronautics. As a matter of tact, even though registered occurrences in ORC have been attributed either to human error or to technology, or to the environment, or sometimes to the combination of these three factors, results of this study conducted in a genealogic-process, socio-anthropological and macro aeronautical technically-systemic approach indicate that the avalanche of air accidents and disasters in ORC is due to "autistic communication", that is, "the normalization of the abnormal, dysfunction, deviances and infringement of standards", thus 'the abnormal standardized" or through communication that proceeds by discrepancies to standards of the International Civil Aviation Organization (ICAO) in a highly regulated and standardized field. The study depicts the evolution of Congolese civil aeronautics since its colonial origins until the present, it immerses itself in the organizations or structures of its "security sector", and outlines the types of communications, interactions, r
Keywords: African Research